2018
DOI: 10.1063/1.5049125
|View full text |Cite
|
Sign up to set email alerts
|

Joint measurability of quantum effects and the matrix diamond

Abstract: In this work, we investigate the joint measurability of quantum effects and connect it to the study of free spectrahedra. Free spectrahedra typically arise as matricial relaxations of linear matrix inequalities. An example of a free spectrahedron is the matrix diamond, which is a matricial relaxation of the 1-ball. We find that joint measurability of binary POVMs is equivalent to the inclusion of the matrix diamond into the free spectrahedron defined by the effects under study. This connection allows us to use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 51 publications
7
53
0
Order By: Relevance
“…The noise set depends on the specific measurements, which makes this measure different than all the other measures considered in this work. It has been investigated in many works [12,28,30,[32][33][34][35][36], often in relation with Einstein-Podolsky-Rosen steering. This specific type of noise has also been considered in scenarios different from incompatibility [37].…”
Section: Incompatibility Depolarising Robustness 311 Definition Anmentioning
confidence: 99%
See 2 more Smart Citations
“…The noise set depends on the specific measurements, which makes this measure different than all the other measures considered in this work. It has been investigated in many works [12,28,30,[32][33][34][35][36], often in relation with Einstein-Podolsky-Rosen steering. This specific type of noise has also been considered in scenarios different from incompatibility [37].…”
Section: Incompatibility Depolarising Robustness 311 Definition Anmentioning
confidence: 99%
“…the measurement generating a uniform distribution of outcomes regardless of the state. It has been investigated in many works [7,28,31,34,35,40], and also in the framework of general probabilistic theories [41,42].…”
Section: Incompatibility Random Robustness 321 Definition and Propmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the authors have found that the inclusion constants for the free spectrahedral relaxation of the 1 -ball, the matrix diamond [DDOSS17], are relevant for the joint measurability of binary quantum measurements [BN18]. The fact that not all observables can be measured at the same time is one of the most remarkable properties of quantum mechanics, the observables of position and momentum providing the best-known example of this behavior [Hei27,Boh28].…”
mentioning
confidence: 99%
“…(See Ref. [BN18] for other recent connections between free spectrahedra and quantum information.) The context of this work is a connection between decompositions of quantum states and decompositions of nonnegative matrices presented in [DN19].…”
Section: Introductionmentioning
confidence: 99%